Retrograde Alteration of Basaltic Rocks in the Þeistareykir High-Temperature Geothermal Field, North-Iceland - Marosvolgyi, Krisztina (2009)
RES Master´s Thesis Hydrothermal alteration of basaltic rocks in a drill core from well ÞR-7 in the geothermal area on Þeistareykir was studied by microscope and X-ray powder diffraction (XRD) methods. Emphasis was laid on the study of clay minerals (sheet silicates) and zeolites formed by hydrothermal alteration. The reservoir rocks in the area are medium to highly hydrothermally altered. The rock forming minerals have been transformed to clay minerals or sheet silicates and several secondary minerals have been precipitated in vugs and factures. Several different clay mineral types were identified in the altered rocks: smectite, chlorite, mixed-layer minerals of of chlorite/smectite, mostly irregular types and irregular chloritic mixed-layer sheet silicates. Smectie/illite mixed-layer minerals were also encountered. The XRD diffraction patterns of the clay mineral samples from well ÞR-7, are quite complex and not easy to interpret, as the minerals are often poorly crystalline and not pure components of any single type of minerals. A regular clay zonation from smectite through mixed layer smectite-chlorite to chlorite, as is common in high-temperature geothermal fields in Iceland, is not observed in the ÞR-7 core. The zeolite types identified in the core are laumontite, yugawaralite, mordenite and wairakite. The zeolite yugawairalite is quite rare and previously only encountered in three localities in Iceland. The higher temperature zeolite wairakite is found in the middle of a zone dominated by the lower temperature zeolite laumontite. Therefore dispersion of the secondary minerals does not show a very clear zonation of the alteration minerals, and correlation to rock temperature is not easily obtained. Some of the clay minerals/sheet silicates encountered suggest a retrograde alteration of previously formed clay minerals at lower temperatures than the original hydrothermal alteration. The occurrence of zeolites in the core implies a similarity to the higher temperature zeolite wairakite that occurs in a ...